2015
DOI: 10.1542/peds.2014-3474
|View full text |Cite
|
Sign up to set email alerts
|

Physician Response to Parental Requests to Spread Out the Recommended Vaccine Schedule

Abstract: OBJECTIVES To assess among US physicians (1) frequency of requests to spread out recommended vaccination schedule for children <2 years, (2) attitudes regarding such requests, and (3) strategies used and perceived effectiveness in response to such requests. METHODS An e-mail and mail survey of a nationally representative sample of pediatricians and family physicians from June 2012 through October 2012. RESULTS The response rate was 66% (534 of 815). In a typical month, 93% reported some parents of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 47 publications
(50 reference statements)
2
71
2
1
Order By: Relevance
“…Furthermore, over half (54%) of pediatricians reported an increased workload as a result of requests for selective vaccination schedules by parents. 33 These trends highlight the need for more specialist referral services to which PCP's can refer families with higher degrees of hesitancy, vaccination knowledge or more complex concerns or requests, such as selective vaccinations schedules. SIC's also able to provide longer appointments and vaccination facilities for these families.…”
Section: Source Of Referralsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, over half (54%) of pediatricians reported an increased workload as a result of requests for selective vaccination schedules by parents. 33 These trends highlight the need for more specialist referral services to which PCP's can refer families with higher degrees of hesitancy, vaccination knowledge or more complex concerns or requests, such as selective vaccinations schedules. SIC's also able to provide longer appointments and vaccination facilities for these families.…”
Section: Source Of Referralsmentioning
confidence: 99%
“…However, a recent survey of pediatricians and family physicians in the US suggested that one third of respondents acquiesced to parental requests for delayed and/or separated vaccinations in the interest of maintaining a therapeutic relationship with the family. 33 This was despite the majority of respondents acknowledging that this placed both the child and community at greater risk of harm from VPD's. 33 The combination of physicians' reported futility in dealing with these requests and the high frequency of this outcome reported in our study emphasize the need for development and training in optimal communication approaches for these discussions.…”
Section: Selective Immunization Schedulesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Although the majority of parents accept vaccines, the increasing frequency of refusal and the requests for alternative vaccine schedules indicate that there are still significant barriers to overcome. 10 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As public confidence in vaccines erodes, [4][5][6][7] parents hesitate about vaccine decisions, vaccination rates may decrease, and outbreaks of vaccinepreventable disease may be more likely. [8][9][10][11] Physicians are highly influential on parental beliefs and attitudes about childhood vaccinations, 7,12-14 yet many feel unprepared to address questions from vaccine-hesitant parents.…”
mentioning
confidence: 99%